Lights, Camera, Action: Integrating Popular Film in the Health Classroom - Diez, Keri S.; Pleban, Francis T.; Wood, Ralph J. (The Journal of school health, 2005)
This article discusses the benefits as well as the important considerations that should be taken into account in integrating popular films in health education classes. Use of popular films in the classroom, termed "cinema education," is becoming increasingly popular in teaching health education. As a matter of convenience, popular films are easy to access, affordable, and most schools have access to supporting materials such as a television and a VCR or DVD. Cinema education can be used to educate students about multicultural issues and diversity sensitivity, both important topics incorporated into a variety of health education subjects. This mode of instruction also allows the instructor to bring historical events to "life" in the classroom and is a viable avenue of instruction for students with low literacy levels. Additionally, this format is one that is familiar to students and can be a source of inspiration and motivation. Students are likely to view these activities as exciting and innovative, which also helps to encourage participation.